Enteric Pathogens and Coinfections in Foals with and without Diarrhea. (27th December 2016) - Olivo, Giovane; Lucas, Thays Mizuki; Borges, Alexandre Secorun; Silva, Rodrigo Otávio Silveira; Lobato, Francisco Carlos Faria; Siqueira, Amanda Keller; da Silva Leite, Domingos; Brandão, Paulo Eduardo; Gregori, Fábio; de Oliveira-Filho, José Paes; Takai, Shinji; Ribeiro, Márcio Garcia
Abstract : Diarrhea is a major clinical problem affecting foals up to 3 months of age. The aim of this study was to identify enteric microorganisms involved in monoinfections and coinfections and the associated virulence factors in healthy and diarrheic foals. Diarrheic (D) (n = 56 ) and nondiarrheic (ND) foals (n = 60 ) up to three months of age were studied. Fecal samples were analyzed for identification of infectious agents (microbiological culturing, molecular techniques, and microscopic analyses). Escherichia coli fimH (30% versus 25%), Salmonella spp. (25% versus 7%), Strongyloides westeri (25% versus 25%), Clostridium perfringens type A (21% versus 10%), E. coli ag43 (20% versus 35%), Strongylus (11% versus 18%), and vapA -positive Rhodococcus equi (5% versus 2%) were the most frequent enteric pathogens detected in D and ND foals, respectively. The frequency of toxin A-positive C. perfringens was significantly increased in the D (p = 0.033 ) compared with the ND animals. R. equi strains harboring virulent plasmids were also identified (VapA 85-kb type I and VapA 87-kb type I) in D and ND foals. Coinfections were observed in 46% of the D and 33% of the ND foals. Our results demonstrate the great diversity of enteric pathogens, virulence factors, and coinfections involved in enteric infections of foals.